The Chinese infrastructural fix in Africa: lessons from the Sino-Zambian 'road bonanza'. (2nd January 2022) - Zajontz, Tim
ABSTRACT: This article scrutinises the surge in Chinese-funded road development in Zambia with the help of David Harvey's theory of spatio-temporal fixes. The 'moving out' of Chinese surplus capital and material to Africa has been facilitated by an extensive disbursement of loans and export credits for infrastructure projects. Transcending Harvey's analytical ' imperio -centrism', the article shows that the actualisation of the Chinese infrastructural fix has been contingent upon Zambia's ambitious, debt-financed infrastructure development agenda. Particularities of Chinese loan financing have thereby fostered 'not so public' procurement processes and accelerated Zambia's rapid debt accumulation. As rising debt has imposed structural constraints, the recent shift in the financial governance of road development towards private project finance is analysed with reference to the Lusaka-Ndola dual carriageway. The renaissance of public-private partnerships and the gradual privatisation of Zambian roads signify new rounds of accumulation by dispossession, as the Chinese infrastructural fix enters its next stage.